Eventos adversos decorrentes do uso da hipodermóclise em pacientes oncológicos sob cuidados paliativos - Clarissa de Jesus Ferraciolli (2022)
Introduction: hypodermoclysis is an ancient technique for administering fluids and medications subcutaneously. In cancer patients under palliative care, it is used for hydration and symptom control. However, studies are still needed to elucidate the incidence and factors related to adverse events. Objectives: to analyze the epidemiological aspects of adverse events resulting from the use of hypodermoclysis in these patients. Method: the study consisted of two stages: a scoping review and a cohort study. First, based on Prisma guidelines, a scope review was carried out in the following databases: Regional Portal of the Virtual Health Library; National Library of Medicine/NLM via Pubmed; Cochrane, Scopus, Web of Science, Embase via Capes Journal Portal, using the descriptors hypodermoclysis, subcutaneous fluid administration, medical Oncology and palliative Care, their Portuguese counterparts and their crossings. Two evaluators independently analyzed the articles. A specific form was used. The second stage involved a concurrent cohort study carried out from November/2020 to January/2022, with 30 patients hospitalized in palliative care. For descriptive analyses, patients were counted only once (n=30). Each of the punctures was analyzed independently, thus making it possible for the same patient to generate more than one puncture data (n=43). For qualitative variables, gross distributions and percentages were calculated, and for quantitative variables, mean and standard deviation. The chi-square and Fisher's exact tests were used to verify the association between sociodemographic and clinical variables and the occurrence of complications. The incidence of adverse events was computed considering the number of new cases as the numerator and the total number of punctures as the denominator. The significance level adopted was 5%. Results: 14 articles were selected, most (71%) were published from 2000 onwards, with the English language being the most prevalent (57%). Observational studies were more frequent, followed by randomized controlled trials. Most studies aimed to evaluate and/or describe the use of hypodermoclysis. The most cited adverse events in the studies were erythema, edema, discomfort at the site, abscess, bleeding, others, extravasation, hematoma and needle displacement. In the cohort study, the incidence of these events was 41.86%, with edema (27.77%) being the most frequent. On average, the time elapsed between the first puncture day and the adverse event was 4.4 days. The most frequent puncture site was the subclavicular region (44.1%), and the non-needled catheter was the most common (90.7%). The most used type of fixation was the transparent film and the main reason for catheter removal was the death of the patient. The prevalent drugs were haloperidol (20.9%) and morphine (15.9%). In the association analyses, the puncture site was identified as a statistically significant factor for the occurrence of adverse events. Conclusion: hypodermoclysis is a useful and safe technique for hydration and drug administration in cancer patients in palliative care, however, in the cohort study, the incidence of adverse events was higher than in other studies in the literature, demonstrating the importance of knowing the factors related to these events and the way to prevent them.